IMPACT OF NATURAL ORGANIC FERTILIZER (SEAWEED SAPS) ON PRODUCTIVITY AND NUTRIENT STATUS OF BLACKGRAM (PHASEOLUS MUNGO L.) - S. K. DWIVEDI; M. R. MESHRAM; A. PAL; N. PANDEY; A. GHOSH (The Bioscan, 2014)
A field experiment was conducted during the Kharif season of 2013 at Research Farm of Indira Gandhi Krishi Vishwavidyalaya, Raipur (Chhattisgarh) to study the effects of seaweed saps on growth, yield, nutrient uptake and economic of Blackgram in Vertisol of Chhattisgarh. The foliar spray was applied twice at different concentrations (0, 2.5, 5.0, 7.5, 10 and 15% v/v) of seaweed extracts (namely Kappaphycus and Gracilaria). Foliar applications of seaweed extract significantly enhanced the growth, yield, nutrient uptake and B:C ratio parameters. The highest grain yield was recorded with applications of 15% Kappaphycus sap + recommended dose of fertilizer (RDF), followed by 15% Gracilaria sap + RDF extract resulting in an increase by 49.2% and 37.8% grain yield, respectively compared to the control (Water spray + RDF). The highest nutrient uptake [nitrogen (N), posphorus (P) and potassium (K)] by crop were observed under 15% K Sap + RDF. The highest net return (‘25,244 ha-1) and B: C ratio (1.27) were observed with the application of 15% Kappaphycus sap + recommended dose of fertilizer RDF.